Study of interleukin‐1 beta expression in acne vulgaris and acne scars. (23rd May 2022) - ElAttar, Yasmina; Mourad, Basma; Alngomy, Hebat‐Allah; Shams El Deen, Aliaa; Ismail, Mayada
Abstract: Background: Acne vulgaris is a multifactorial disease that mostly heals by scarring. Interleukin‐1 beta (IL‐1β) is a proinflammatory cytokine, suggested to play a key role in acne pathogenesis. Objective: To study the immunohistochemical (IHC) expression of IL1β in acne vulgaris and acne scars to evaluate its possible role in their pathogenesis and to study the relation between the expression of IL1β and the clinicopathological parameters. Patients and methods: This study was conducted on sixty subjects (twenty patients with acne vulgaris and twenty patients with acne scars), and twenty healthy volunteers as controls. Skin biopsies were taken from patients and controls for routine histopathological examination with hematoxylin and eosin stain and IHC staining of IL‐1β. Results: There was a statistically significant increase in expression of IL‐1β in acne vulgaris compared with post‐acne scars and controls, ( p < 0.001) for both. IL‐1β expression was significantly positively correlated with both clinical severity of acne vulgaris ( p = 0.022) and severity of histopathological inflammation ( p = 0.011). Conclusion: Interleukin‐1β expression was associated with acne vulgaris and post‐acne scars with significant positive correlation to clinical and histopathological severity of acne vulgaris. Thus, IL‐1β could be a key player cytokine in acne pathogenesis, its severity and development of post‐acne scars.